2021
DOI: 10.1111/ors.12665
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the role of intra articular injection of platelet‐rich fibrin in the management of temporomandibular joint osteoarthritis: A STROBE compliant retrospective study

Abstract: Osteoarthritis (OA) is a debilitating disease. A number of treatments like conservative approach, minimally invasive procedures and surgical therapy have proved to be beneficial. However, there is no consensus regarding the use of a single modality of treatment.How to cite this article: Bera RN, Tiwari P. Evaluating the role of intra articular injection of platelet-rich fibrin in the management of temporomandibular joint osteoarthritis: A STROBE compliant retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…75 In another study, the effects of intra-articular i-PRF injections on the treatment of osteoarthritis of the TMJ were assessed. 76 In this study, it was revealed that while i-PRF did not alleviate TMJ pain after 6 months, repeated injections did positively impact maximal mouth opening. Ghoneim and colleagues also compared the effectiveness of arthrocentesis with/without i-PRF injections for the treatment of TMJ disc displacement and reduction.…”
Section: Clini C Al Us E Of I-prf For Tmj Injec Tionsmentioning
confidence: 65%
See 1 more Smart Citation
“…75 In another study, the effects of intra-articular i-PRF injections on the treatment of osteoarthritis of the TMJ were assessed. 76 In this study, it was revealed that while i-PRF did not alleviate TMJ pain after 6 months, repeated injections did positively impact maximal mouth opening. Ghoneim and colleagues also compared the effectiveness of arthrocentesis with/without i-PRF injections for the treatment of TMJ disc displacement and reduction.…”
Section: Clini C Al Us E Of I-prf For Tmj Injec Tionsmentioning
confidence: 65%
“…At the 3‐month follow‐up, substantial improvements in VAS and Helkimo clinical dysfunction scores were reported, along with improvements in the maximum incisal opening of the patients 75 . In another study, the effects of intra‐articular i‐PRF injections on the treatment of osteoarthritis of the TMJ were assessed 76 . In this study, it was revealed that while i‐PRF did not alleviate TMJ pain after 6 months, repeated injections did positively impact maximal mouth opening.…”
Section: Clinical Use Of I‐prf For Tmj Injectionsmentioning
confidence: 99%